Novel superhydrophobic and superoleophilic sugarcane green ceramic hollow fibre membrane as hybrid oil sorbent-separator of real oil and water mixture - Jamalludin, Mohd Riduan; Hubadillah, Siti Khadijah; Harun, Zawati; Othman, Mohd Hafiz Dzarfan; Yunos, Muhamad Zaini (Elsevier, 2019)
The frequent oil spill accidents in nowadays has aroused great attention all over the world. Superhydrophobic and superoleophilic grafted on various substrates have attracted much attention to treat oil and water mixture because of their unique performance that can effectively separate oil and water mixture. At the same time, ceramic membrane also shows potential substrates to be used in treating oil and water mixture. However, conventional ceramic membrane that made from alumina show drawbacks in term of its high cost production. Herein, we report a new ceramic membrane that derived from agricultural-sugarcane bagasse waste and modified into superhydrophobic and superoleophilic to act as hybrid oil sorbent and separator. In this study, we successfully treat three types of real oil and water mixture from palm oil mill effluent (POME), restaurant and car wash with oil rejection and flux up to 99% and 134 L/m2h, respectively. In summary, this work demonstrates a facile, economic and effective method to fabricate superhydrophobic and superoleophilic substrates for oil and water separation.